Traveling and writing back: two Muslim women in early twentieth-century London - Hasan, Md. Mahmudul (2022)
Atiya Fyzee and Zeyneb Hanoum embarked on two unrelated journeys to Europe with enormous fascination for the continent and its people. Their presence in Europe modified their expectations and perceptions of Europeans and their native ways of life. While they appreciated many aspects of their native and host cultures, they also expressed disappointment with failures and shortcomings in both. Even though in their memoirs they shared a heightened fascination for London, both were equally reluctant to call it “home”. Their temporary diasporic experiences in the metropolis put them in the context and vantage position of the “third space” from which they looked at both cultures critically. Importantly, their memoirs present counter-narratives to the West, as both wrote back to Western imperialist and orientalist conceptions of their respective societies. In the early twentieth century, as a tool of imperialist and colonial domination, the Western caricaturing of Eastern cultures and peoples was part of the mainstream narrative; and counter-voices and counter-images were mostly outmaneuvered or wrapped in silence. Hence, Atiya’s and Zeyneb’s counter-narratives were ground-breaking and revolutionary. Their unease with the dominant Western misrepresentation of Eastern societies, perhaps, pointed to a simmering but larger intellectual movement that was gaining momentum globally to question the validity of the Western master narrative.